Editorial - Kadankavil, Thomas (Journal of Dharma, 1991)
Reflective men will agree that gender justice requires freedom and equality for women. It means the relation between man and woman must be a relation of genuine mutuality, concern and respect To make thls relation possible the demand of the militant feminists is that the women must have enough economic, social, political, and psychological Independence as its preconditions. Mutual renunciation of the use of power on the basis of equality of power is another necessary precondition that the breakdown of the relation may not leave the women, as usual, in a position to be overpowered.